SYNTHESIS, CHARACTERIZATION, AND ACTIVITY ASSESSMENT OF AMOXICYLIN/CuO COMPOUNDS AGAINST PATHOGENIC BACTERIA - Hadi Barru Hakam Fajar Siddiq; Siti Nur Azizah (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
Infection is a disease caused by bacteria. Some bacteria that can cause infection are Escherichia coli, Salmonella typhi, Staphylococcus aureus, and Bacillus subtilis. Infection can be prevented by antibiotic therapy. Excessive use of antibiotics such as misuse of indications, free use in the community, inappropriate doses, and timing of application will cause new problems such as increasing bacterial resistance to antibiotics. The prevalence of drug-resistant bacteria is increasing in many parts of the world. However, this increase is accompanied by a downward trend in the development of new antibiotics. Thus, to overcome this problem new antibiotics have to be developed. This study aimed to synthesize a new antibiotic, namely to test amoxicillin/CuO and its antibacterial activity against E. coli, S. typhi, S. aureus, and B. subtilis. Antibacterial activity test using disc diffusion method. The XRD characterization results showed that the diffraction peaks of amoxicillin/CuO in the image above started from 21.13; 29.54; 30.67; 36.82; 39.5; 42.05; and 47.88. The SEM results of the Amoxicillin/CuO compound showed that the particle size of the compound was still in the form of a graph of 196-345 nm. The results of testing the antibacterial activity of amoxicillin/CuO compounds against E. coli, S. typhi, B. subtilis, and S. aureus showed that amoxicillin/CuO compounds had activity against all bacterial samples. Thus, amoxicillin/CuO compounds can be used as antibacterial therapy.